2011
DOI: 10.1155/2011/524520
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Tolerability, and Acceptability of Iron Hydroxide Polymaltose Complex versus Ferrous Sulfate: A Randomized Trial in Pediatric Patients with Iron Deficiency Anemia

Abstract: Iron polymaltose complex (IPC) offers similar efficacy with superior tolerability to ferrous sulfate in adults, but randomized trials in children are rare. In a prospective, open-label, 4-month study, 103 children aged >6 months with iron deficiency anemia (IDA) were randomized to IPC once daily or ferrous sulfate twice daily, (both 5 mg iron/kg/day). Mean increases in Hb to months 1 and 4 with IPC were 1.2 ± 0.9 g/dL and 2.3 ± 1.3 g/dL, respectively, (both P = 0.001 versus baseline) and 1.8 ± 1.7 g/dL and 3.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 20 publications
1
48
0
8
Order By: Relevance
“…IPC, a drug which was developed and promoted as having fewer or none adverse effects has had mixed fortunes. Some studies like the present one have shown its efficacy in raising the Hb almost equally well compared to ferrous sulfate or other salts [8,9]. However, other studies have shown the response with IPC being none or poorer than the comparator salts.…”
mentioning
confidence: 48%
“…IPC, a drug which was developed and promoted as having fewer or none adverse effects has had mixed fortunes. Some studies like the present one have shown its efficacy in raising the Hb almost equally well compared to ferrous sulfate or other salts [8,9]. However, other studies have shown the response with IPC being none or poorer than the comparator salts.…”
mentioning
confidence: 48%
“…Beide Gruppen unterschieden sich im Ausgangs-Hb vor Therapie, der in der Gruppe mit später persistierender Anämie deutlich niedriger war: 8,4 (5,4 -11,1) g/dl vs. 10,6 (6,9 -11,3) g/dl (p < 0,0005). (7,(19)(20)(21). Da individuelle Behandlungsverläufe aus dem klinischen Alltag ausgewertet wurden, nicht jedoch Daten einer prospektiven Studie mit festen Untersuchungszeitpunkten etc., ergibt sich erwartungsgemäß eine breite Streuung der zur Beurteilung der Wirksamkeit der EPK-Therapie erfassten Parameter.…”
Section: Patienten Und Methodenunclassified
“…Aufgrund der geringen Zahl randomisierter pädiatrischer Studien, die zudem unterschiedliche Patientengruppen untersuchten, ist eine Metaanalyse nicht verfügbar. Die meisten Studien erbrachten Ergebnisse analog zu denen bei erwachsenen Patienten (11)(12)(13)20). Eine Studie zeigte hingegen für EPK bei einer Studiendauer von 30 Tagen kein signifikantes Therapieansprechen (25).…”
Section: Diskussionunclassified
“…In 2 pediatric trials, iron-polymaltose complex and ferrous sulfate were equally effective. 10,11 However, Bopche and colleagues documented better hemoglobin response to ferrous sulfate in another trial; hemoglobin levels decreased in 11 of 53 children receiving ironpolymaltose complex. 12…”
Section: Iron Complexesmentioning
confidence: 99%